Secretagogin expression in the mouse olfactory bulb under sensory impairments - L. Pérez-Revuelta (Nature Portfolio, 2020)
Abstract The interneurons of the olfactory bulb (OB) are characterized by the expression of different calcium-binding proteins, whose specific functions are not fully understood. This is the case of one of the most recently discovered, the secretagogin (SCGN), which is expressed in interneurons of the glomerular and the granule cell layers, but whose function in the olfactory pathway is still unknown. To address this question, we examined the distribution, generation and activity of SCGN-positive interneurons in the OB of two complementary models of olfactory impairments: Purkinje Cell Degeneration (PCD) and olfactory-deprived mice. Our results showed a significant increase in the density of SCGN-positive cells in the inframitral layers of olfactory-deprived mice as compared to control animals. Moreover, BrdU analyses revealed that these additional SCGN-positive cells are not newly formed. Finally, the neuronal activity, estimated by c-Fos expression, increased in preexisting SCGN-positive interneurons of both deprived and PCD mice -being higher in the later- in comparison with control animals. Altogether, our results suggest that the OB possesses different compensatory mechanisms depending on the type of alteration. Particularly, the SCGN expression is dependent of olfactory stimuli and its function may be related to a compensation against a reduction in sensory inputs.